Assessment of the epidemic preparedness and response capacity in Sierra Leone - Mohamed Vandi; Delia Akosua Bandoh; Kofi Mensah Nyarko; Tete Amouh; Virgil Kuassi Lokossou; Simon Antara (Journal of Interventional Epidemiology and Public Health)
Introduction: In recent times, natural disasters and disease outbreaks have struck various countries increasing morbidity and mortality rates. Sierra Leone, one of the three West African countries that was hit greatly by the 2014 Ebola Virus Disease (EVD) outbreak was not adequately prepared for the outbreak. As parts of efforts to improve preparedness and response to public health in West Africa, The Economic Community of West African States (ECOWAS) adopted approaches such as strengthening of their disease surveillance systems through capacity development and implementing the International Health Regulations, 2005. Objective: We assessed the epidemic preparedness and response capacity of Sierra Leone three years after the EVD outbreak. Methods: We conducted interviews with various representatives of the major stakeholders involved in the emergency preparedness and response and carried out record reviews in Sierra Leone from April to July 2018. Results: Sierra Leone has a number of effective plan and policies developed and implemented to improve epidemic preparedness and response. The directorate of Health Security and emergencies under the Public health directorate of the ministry of health provides overall coordination of public health emergency preparedness and response in the country. Conclusion: Sierra Leone has made some significant strides on public healthrelated efforts since the 2014 outbreak. However, the absence of an EOC serves as a limiting step to achieving the required preparedness the country needs. Again, over reliance on international partners could affect to the sustainability of their gains made if not addressed effectively.